Fostering creativity in teaching diploma programs - Ribeiro, Rejane Arruda; Fleith, Denise de Souza (Paidéia (Ribeirão Preto), 2007)
This study examined the perception of 82 professors from teaching diploma programs in the Federal District, Brazil, regarding the extent to which their educational practices favor the development of their students' creative expression, as well as potential barriers to their personal creativity. The study also examined the perception of 1396 students regarding their professors' educational practices. The Educational Practice and the Barrier Identification to Personal Creativity Inventories were applied. The results revealed that the professors' perception concerning to what extent their educational practices encourage students' creative expression was more favorable than that of students. Furthermore, the perception of students in advanced semesters was more favorable than that of those in first semesters in relation to the factors measured in the Educational Practice Inventory. Students from private institutions evaluated more positively the factors measured by this inventory than students from public institutions. Professors appointed lack of time/opportunity as the main barriers to personal creativity.